Gastroesophageal reflux in lockdown - Hafez Al-Momani; Dua'a Al Balawi; Muna Almasri; Hadeel AlGhawrie; Lujain Ibrahim; Lena Adli; Hadeel Al Balawi; Sameer Al Haj Mahmoud (Future Science OA, 2023)
Aim: This study examines the changes in gastroesophageal reflux disease (GERD) symptom frequency among patients with GERD throughout the COVID-19 pandemic. Methods: A structured questionnaire was distributed among 198 GERD patients. The questionnaire consisted of a demographic characteristic assessment, the GerdQ questionnaire, and a reflux symptom index (RSI) questionnaire. Result & conclusion: A statistically significant increase in GerdQ score was identified among participants during the COVID-19 pandemic (t = 7.055, df = 209, p < 0.001), who had experienced an increase in the frequency of positive predictors of GERD and a decrease in the frequency of negative predictors of GERD. The COVID-19 pandemic and its related lockdown countermeasures may have led to exacerbating and worsening GERD symptoms.